Numerical Investigation of Pool Boiling Under Ocean Condition with Lattice Boltzmann Simulation. Part Ⅱ: Rolling Condition - Zou, Qifan; Liu, Xiuliang; Hu, Yongyan; Chang, Yuxuan; Li, Pengkun (Frontiers in Energy Research, 2021)
Rolling motion caused by ocean condition will induce more complicated inertial forces with their force directions changing all the time, which results more complex bubble behaviors and unique heat transfer characteristics. In this work, pool boiling under rolling condition is numerically simulated using multiple relaxation time phase change lattice Boltzmann method (LBM). Pool boiling patterns, boiling curve of time-averaged heat flux, transient heat flux and rolling effects on different pool boiling regions are investigated. The results show that pool boiling curve of time-averaged heat flux between rolling condition and static condition are not obvious until close to critical heat flux, and 9.3% higher CHF is achieved under rolling condition while worse heat transfer is discovered at film boiling. Moreover, distinct fluctuation of transient heat flux of pool boiling under rolling condition is found for all boiling regimes, and its variation pattern along with the rolling motion and bubble behavior is investigated. Furthermore, tangential inertial force caused by rolling motion has positive influence on heat transfer of pool boiling, while the centrifugal force has negative influence on heat transfer, since it is opposite to the gravity and hence decreases the buoyancy force. Besides, larger rolling amplitude and smaller rolling period will induce larger additional inertial forces, and thus make greater influences on the bubbles’ behavior and pool boiling heat transfer.